The Hudaibiyah Treaty as a Model for International Treaty Law: Analysis of Siyasah Fiqh and its Relevance for Public Law - Palupi, Dwi Astuti; Iffan, Ahmad (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study analyzes the Treaty of Hudaybiyyah (6 AH) as a case study in the conception of international treaty law, framing it within the principles of Fiqh Siyasah (Islamic political jurisprudence). The research aims to identify the public law principles contained within the treaty and examine their relevance as a source for enriching contemporary international law. Using a qualitative-normative research method with a library-based approach. Primary sources consist of hadith collections, sirah literature, and classical works on fiqh al-siyasah; secondary sources include books, journal articles, and contemporary studies. Data collection employs library research, and the analysis applies a qualitative-comparative and normative-historical approach. The findings indicate that the Treaty of Hudaybiyyah not only represents a historical event but also serves as a model of diplomacy that emphasizes dialogue, adherence to agreements, and the protection of human rights (particularly in the context of conflict resolution). This analysis reveals that these principles align with several modern international law tenets, such as pacta sunt servanda and the peaceful settlement of disputes. Therefore, this study argues that a review of the Treaty of Hudaybiyyah through the lens of Fiqh Siyasah can provide a significant theoretical contribution to enrich the discourse on public law, while also affirming the relevance of Islamic intellectual heritage as a source of inspiration for shaping a more just and peaceful global order.